Development of a Unique Student Pharmacist Internship in a Primary Care Provider System - Norman E. Fenn; Natalie R. Gadbois; Gwen J. Seamon; Shannon L. Castek; Kimberly S. Plake (MDPI AG, 2019)
Purpose: To describe a unique pharmacy intern program in a group of federally qualified health center (FQHC) outpatient primary care provider clinics. Summary: A pharmacy intern program was created at the North Central Nursing Clinics in Indiana, a group of four FQHC outpatient primary care provider facilities. Intern-performed tasks included: Prior authorization (PA) requests, medication assistance program (MAP) applications, sample procurement and inventory, and contraceptive devices for implantation inventory management. Interns interacted with clinic administration, nurse practitioners, and medical staff to complete their assigned responsibilities. Over a one-year period, the interns completed documentation on more than 2000 charts during a combined 12 h a week. Interns identified the interprofessional interactions as the most beneficial experience, while providers acknowledged no difference in the processing of paperwork during the transition of duties from pharmacy fellow to intern. Conclusion: This unique pharmacy intern program was successfully created and implemented in a primary care provider office, resulting in learning opportunities for pharmacy interns, as well as operational efficiencies to fellows, providers, and the organization.